Treatment options for Indonesian triple negative breast cancer patients: a literature review of current state and potentials for future improvement - Ibnu Purwanto; Iwan Dwiprahasto; Teguh Aryandono; Sofia Mubarika (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Triple negative breast cancer (TNBC) is still associated with grave prognosis, especially compared to other breast cancer subtypes. Advances in medical science have improved our understanding on the biological nature and heterogeneity of TNBC, explaining the efficacy variability of existing chemotherapeutic drugs on TNBC patients. Complexity of TNBC has led to wide variation of TNBC treatment across the globe, resulting in unsatisfactory treatment outcome. This issue is further complicated by the absence of TNBC treatment guideline in many countries, including in Indonesia. This review discusses systemic treatment options for TNBC while taking account its molecular heterogeneity. Specific consideration is made for Indonesia, not only for current clinical practice, but also for future improvements. Immunotherapy, especially programmed cell death 1 (PD-1/PD-L1) inhibitor, has recently shown promising result in TNBC patients. It can be concluded that TNBC is heterogenous and treatment option should be tailored based on its molecular profile.